Remote Monitoring: How to Maximize Efficiency through Appropriate Organization in a Device Clinic - Massimiliano Maines; Giancarlo Tomasi; Luisa Poian; Marzia Simoncelli; Debora Zeni; Monica Santini; Maurizio Del Greco (Journal of Cardiovascular Development and Disease)
Introduction: Remote device monitoring is indicated under class I A standard of care according to the latest HRS/EHRA/APHRS/LAHRS Expert Consensus Statement on Practical Management of the Remote Device Clinic. Despite this strong endorsement and the supporting data, the adoption of remote monitoring practices remains lower than expected. One cause of the underutilization of telemonitoring devices is work overload. Thus, a crucial point for improving the adoption of remote monitoring systems is ensuring their sustainability. Materials and Method: After analyzing the resources necessary to manage a device telemonitoring clinic, we initiated a process to reduce redundant transmissions: 1. eliminated scheduled loop recorder transmissions, retaining only alert transmissions; 2. reduced the frequency of the scheduled transmissions of pacemakers from four to one per year and the scheduled transmissions for defibrillators from four to two per year; and 3. optimized and customized the programming of device alerts with two primary interventions. Results: These strategies allowed us to significantly reduce the number of transmissions/patient/year from 7.3 to 4.7. The first change was made in January 2020, which eliminated scheduled transmissions for loop recorders, reduced transmissions per patient from 14 to 10.4 for loop recorders, and decreased global transmissions per patient from 7.6 to 6.5. The subsequent adjustment in January 2021, which reduced the scheduled transmissions of pacemakers and defibrillators, further lowered transmissions per patient from 6.5 to 5.2 for pacemakers and from 4.7 to 3.1 for defibrillators. Additionally, enhanced attention to device reprogramming starting in January 2022 resulted in a further reduction in transmissions per patient from 5 to 4.7. Conclusion: Carrying out some simple changes in the number of scheduled transmissions and optimizing the programming of the devices made it possible to reduce the number of transmissions and make the remote monitoring of the devices more sustainable